2005
DOI: 10.1002/pssa.200521169
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bi2Sr2CaCu2O8 surfaces cleaved at low temperature and at room temperature from secondary ion mass spectrometry and work function measurements

Abstract: Secondary ion mass spectrometry (SIMS) and work function measurements were made to examine the surface composition difference between Bi2Sr2CaCu2O8 surfaces that were cleaved at low temperature and at room temperature. SIMS measurements of the surfaces cleaved at room temperature indicated that the intensity of secondary ions Ca+, Sr+, and Cu+ increases and the intensity of O– decreases with time. More‐ over, the work function increased with time. On the other hand, SIMS of the surfaces cleaved at low tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Saito et al found the work function of BSCCO to be 4.849 eV at 85 K, and that it rose by about 0.1 eV when the sample was allowed to warm to 130 K. 17 Although we did not monitor the work function while heating, if we assume that the overall work function does indeed change upon heating as reported, the absence of any temperature dependence to the neutralization suggests that the normally emitted Na probes only a local part of the electrostatic potential, namely that around the Bi atoms themselves, and that this potential is unaffected by annealing. The effect of annealing may involve diffusion of oxygen from the bulk to fill in vacancy defects at the surface, which would be consistent both with the positive change in the work function and the insensitivity of the Bi SSP neutral fraction to the temperature.…”
Section: Time-of-flight Results For a Pristine Bscco-2212 Surfacementioning
confidence: 99%
“…Saito et al found the work function of BSCCO to be 4.849 eV at 85 K, and that it rose by about 0.1 eV when the sample was allowed to warm to 130 K. 17 Although we did not monitor the work function while heating, if we assume that the overall work function does indeed change upon heating as reported, the absence of any temperature dependence to the neutralization suggests that the normally emitted Na probes only a local part of the electrostatic potential, namely that around the Bi atoms themselves, and that this potential is unaffected by annealing. The effect of annealing may involve diffusion of oxygen from the bulk to fill in vacancy defects at the surface, which would be consistent both with the positive change in the work function and the insensitivity of the Bi SSP neutral fraction to the temperature.…”
Section: Time-of-flight Results For a Pristine Bscco-2212 Surfacementioning
confidence: 99%
“…An original approach for monitoring this oxidation was based on the measurement of the work function using the contact potential between two metals. 149 The applicability of the method was shown for Bi 2 Sr 2 CaCu 2 O 8 , a cooling superconductor that was known to be extremely sensitive to surface oxidation. The close correlation between the time dependence of the Ca + , Cu + , O À and Sr + secondary ion intensities for in situ cleaved samples, kept at room temperature or at 100 K for up to 2 h, and that of the contact potential strongly supported the use of the developed method to measure the surface work function.…”
Section: Analytical Methodologymentioning
confidence: 99%
“…Bi, however, has a low miscibility, and at the surface is likely to be highly mobile. Oxygen, too, is apt to migrate from lower layers to the surface, which has been suggested to explain the results of SIMS studies of Bi-2212 [8].…”
Section: Resultsmentioning
confidence: 95%
“…Furthermore, there is evidence to suggest that oxygen in Bi-2212 is highly mobile in vacuum, diffusing from the bulk to the surface [8,26]. In addition, the work function would be expected to decrease if oxygen were being removed from the outermost layer, while in fact the work function increases as steady-state is attained.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation